Automobile air-conditioning teaching kit (R-134a system) / Ismarullizam Mohd Ismail - Mohd Ismail, Ismarullizam (2003)
In this project, our main objective is to produce a training rig for the following automobile air-conditioning systems viz, the R134a and R12 system as a teaching kit. Besides that, we have to learn about the installation and inspection of both of these systems. On this project, we started by disassembling and overhauling the R-12 and R134a systems with the right tools. Servicing the parts give us knowledge about the parts, their functions, and their designs. Reassembling back all the parts and components is one of the more important aspects of this work. One has to prevent carelessness in putting back all the parts. The air-conditioning system can be mounted on the frame and will be tested for its performance. Lastly, a design of the rig to run under both systems have been carried out. Construction of the prototype rig costs approximately RM 6000 and took one year to design and fabricate. The completed rig has been assembled with a panel board showing the principle operation of these systems which are mounted on the frame, and an operations manual which included a description on servicing, overhauling and trouble diagnosis needs of the systems has been produced. The benefits of this project are that we learn not only its operation, but the servicing, overhauling and inspection of the R- 12 & R134a systems as well.